Ultrastructural alterations in thyrocytes of zebrafish (Danio rerio) after exposure to propylthiouracil and perchlorate - Schmidt, Florian; Wolf, Raoul; Baumann, Lisa; Braunbeck, Thomas (Toxicologic pathology, 2017)
Histopathology is a widely used approach to evaluate effects of endocrine-active chemicals in the thyroid. However, effects at an ultrastructural level have hardly been examined in fish thyroids. In the present study, zebrafish was exposed to sublethal concentrations of propylthiouracil (PTU; 0-50 mg/L) and perchlorate (PER; 0-5,000 µg/L) for 5 weeks in a modified early life-stage test. None of the treatments caused significant mortality (no observed effect concentrations for survival ≥50 mg/L [PTU] and ≥5,000 µg/L [PER]). PTU induced dose-dependent alterations in the rough endoplasmic reticulum (rER) in all exposure groups, whereas only the 2 highest PER exposure groups (500 and 5,000 µg/L) resulted in alterations of the rER. Both substances caused an increase in the numbers of lysosomes and mitochondria, with mitochondria displaying distorted cristae. Increased mitochondrial diameters were only observed in the PTU treatment. PER-exposed samples displayed an increase in apical microvilli. The highest PTU concentration (50 mg/L) showed first signs of cellular degeneration. Ultrastructural changes in zebrafish thyrocytes thus appear specific for different chemicals, most likely depending on their specific modes of action. Additional knowledge of subcellular changes in thyrocytes can help to better understand and interpret existing histological data in the future.